Emerging Drying Technologies and Their Impact on Bioactive Compounds: A Systematic and Bibliometric Review - Amanda Aparecida de Lima Santos; Gabriela Fonsêca Leal; Matheus Robim Marques; Lucas Caiafa Cardoso Reis; João Renato de Jesus Junqueira; Leandro Levate Macedo; Jefferson Luiz Gomes Corrêa (Applied Sciences)
Drying is a key method for food preservation; however, conventional techniques often lead to the degradation of bioactive compounds, compromising nutritional quality. This systematic review, following the PRISMA protocol, examines emerging food drying technologies designed to enhance process efficiency while preserving nutritional and functional properties. A bibliometric analysis was conducted to identify research trends from 2014 to 2024. Searches were performed in the Scopus and Web of Science databases accessed on 17 January 2025, including only original research articles published in English focusing on food drying applications. Reviews, editorials, and studies unrelated to the food sector were excluded. Due to the technological nature of the outcomes, a formal risk of bias assessment was not applicable. This review highlights several emerging drying technologies, such as microwave, radiofrequency, infrared, ultrasound, freeze-drying, and cold plasma. The qualitative synthesis indicates these technologies improve the retention of phenolics, flavonoids, and vitamins, thus enhancing nutritional stability. Nevertheless, challenges remain in industrial-scale implementation, particularly regarding the economic feasibility and optimization of operational parameters. This review received no funding and was not registered in any public database. The findings underscore the need for continued research to develop sustainable and functional dried food products that meet current market demands and consumer expectations.